Manual de aplicación de normas de seguridad y salud ocupacional a trabajadores de parques y jardines del Gobierno Autónomo descentralizado Chone - Hidalgo Reina, Claudia Narcisa (2018)
The purpose of the research was to design a manual for the application of safety and occupational health standards to workers in parks and gardens of Chone Decentralized Autonomous Government, taking into account that, according to laws established within the Constitution of the Republic, the Safety Social Law, Labor Code, Regulation of the Andean Instrument for Safety and Health at Work, Regulation of Safety and Health of Workers and Improvement of the Work Environment and even the International Labor Organization, determine the workers health and safety as main priority, that is why through research techniques (interview, surveys and observation form) it was possible to identify the risks (physical and chemical) to which the workers of the Subdirectorate, who are in danger, are exposed in their daily work. Based on these risks, the manual was designed, taking into account criteria of the same workers and those in charge of the Subdirectorate, its structuring and socialization was done with the purpose of prioritizing and safeguarding the health of the workers and mitigating the insecurities to those who are exposed.